International collaboration in endourology: multicenter evaluation of prestenting for ureterorenoscopy - Jessen, Jan Peter; Knoll, Thomas (Journal of endourology, 2016)
Introduction: Semirigid and flexible ureterorenoscopy (URS) procedures are safe and efficient treatment options for urolithiasis of all localizations. Sometimes, a Double-J stent is placed in preparation of definitive treatment. The aim of our study was to evaluate the influence of prestenting on the outcome of URS.Patients and Methods: We retrospectively analyzed 565 patients of our prospective, multicenter multinational database who underwent URS for renal or ureteral stones from June 2011 to December 2013. Demographic and stone-related data, surgery time, stone clearance, and complications were evaluated. Statistical analysis was performed comparing the prestented and nonstented groups.Results: Demographic data, stone size, and localization were comparable in both groups. Three hundred twenty-three patients were prestented and 242 nonstented. Overall, prestenting had significant influence on the stone-free rate (SFR) (86% prestented vs 74% not prestented, p = 0.0003) and complication rate (6.5% vs 14.5%, p = 0.003), but not on surgery time (55 ± 36 minutes vs 61 ± 35 minutes, p = 0.071). Subgrouped, this was also true for renal stones (83% vs 60%, p = 0.0001, odds ratio [OR] 3.15; confidence interval, CI [1.77, 5.62]/8.7% vs 19.4%, p = 0.02, 0.39 [CI 0.19, 0.83]). For ureteral stones, there was no significant influence on SFR (94% vs 90%, p = 0.4, OR 1.63 [CI 0.63, 4.22]), but significantly more complications (3.1% vs 10.7%, p = 0.02, OR 0.27 [CI 0.08, 0.86]) in the nonstented group.Conclusion: Prestenting positively affects safety and efficacy of URS. This is more pronounced in the treatment of kidney stones compared with ureteral stones. Although the SFR for ureteral stones is comparable without prestenting, the complication rate is higher.
Gesehen am 31.10.2019